Vocabulary Learning Strategies Used by Undergraduate Students - Herlina Lindaria Simanjuntak (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2021)
Vocabulary is a tool for clarification of thinking, clearing, and satisfying expression of ideas. Hence, the research aims at investigating Vocabulary-learning strategy by EFL students. The data were collected by using questionnaires and interviews. This research employed a descriptive method by examining O’Malley and Chamot’s strategies (2004). The results show that the common strategies used by learners in vocabulary learning namely Reading short stories, Reading loudly, Repeating after the lecturers, Using English social media, Making list of memorized vocabulary, Skipping new word which likely does not need to study, Watching movie, Listening the song, Applying new words in the sentences, Making conversation with friends in and outside the classroom, Writing the word repeatedly, Asking the lecturers or classmates who understand more than them, and Asking the lecturers to translate the meaning of a word. Meanwhile, the strategies to develop their English vocabulary such as Writing the repeated word, Discovering the meanings of new words by using the dictionary, Memorizing new vocabulary, Saying the word loudly in front of the mirror, and Using English social media.